Quadros de ação coletiva e redes sociais digitais: o caso do João Pessoa Avante - Carvalho, Átila Andrade de (2017)
This academic work sought, in the first place, to analyze the role of digital social networks, in particular Facebook at the June 2013 public protests, as a sphere of collective action, noting the impact of online participation of individuals in the construction of mobilization events in the city of João Pessoa-PB. For that, a meso-analysis of three events on Facebook, named João Pessoa Avante II, III and IV, was carried out, taking into account the sociopolitical context in which the manifestations emerge, as well as the postings of the participants of the online events, together with the events calls . The study was based on political sociology in particular linked to the theory of new social movements, reflecting critically the theory of collective action frameworks, in relation to the concept of political confrontation. The research was oriented by an interactionist perspective with emphasis on the confrontation of interpretations, prioritizing the discursive interactions between the online participants of the events on Facebook and the way of alignment with the interpretations of the social movements in the street, characterizing a study of the relational type in the field of political sociology. The study, in a second plan, sought to observe the limits of the application of the concept of collective action frameworks focused on the analysis of social mobilization in the universe of digital social networks.